Ethiopia Climate Change and Food Security meeting, Addis Ababa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
In early July CCAFS East Africa Regional Theme co-sponsored a national awareness raising conference at the Ghion Hotel in Addis Ababa, Ethiopia titled “Climate Change Vulnerability and Risk Assessment of Agriculture and Food Security in Ethiopia: Which Way Forward?” The co-hosts of the event were the Ethiopian Ministry of Agriculture (MoA), Climate Change Forum – Ethiopia (CCF-E), and the United States Agency for International Development (USAID).